Comparison of 5vs5 training games and match-play using microsensor technology in elite basketball - Svilar, L.; Castellano, J.; Jukic, I. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to compare the data obtained using microsensor technology in 2 types of 5vs5 training games—the regular-stop game (RSG) and the no-stop game (NSG)—and in match-play (MP) in elite basketball. Sixteen top-level basketball players were monitored during pre- and in-season periods (10 weeks). The variables included: player load, accelerations (ACC), decelerations (DEC), changes of direction (CoD), and jumps (JUMP)—all in both total (t) and high-intensity (h) relative values (i.e., per minute of play): PLmin, ACCmin, DECmin, CoDmin, and JUMPmin, respectively. Almost all variables showed trivial difference between MP and RSG. The only variable that showed small difference was tACCmin (MP > RSG). In case of RSG vs. NSG, 3 variables showed trivial difference—tACCmin, hACCmin, and hDECmin, 3 (i.e., hCODmin, tDECmin, and PLmin) small differences, and 3 (tCoDmin, tJUMPmin, and hJUMPmin) moderate differences (NSG > RSG). In MP vs. NSG, 2 variables (hCoDmin and tACCmin) showed trivial differences; variable hDECmin showed small difference, whereas the other 5 variables (tCoDmin, tJUMPmin, hJUMPmin, tDECmin, and PLmin) showed moderate difference (NSG > MP). Only one variable, hACCmin, showed moderate difference, when MP > NSG. The main conclusion of the study was that by introducing some constraints into 5vs5 tasks, the coaching staff could elicit higher physical demands than those occurring in MP. By understanding the differences in demands of NSG, RSG, and MP, coaches in elite basketball can improve their system of training drills selection, especially when looking for optimal short-term tapering approach, leading up to the game day.